PROBLEMS OF THE PREOPERATIVE DIAGNOSIS OF LOW-GRADE THYROID CANCER SPREADING TO CERVICAL LYMPH NODES AND WAYS OF THEIR SOLUTION - S. S. Seryogin; A. I. Bezhin; V. V. Khvostovoy (Опухоли головы и шеи, 2015)
To estimate the regional spread of low-grade thyroid cancer (TC) is a topical problem. The paper analyzes the problems of preoperative diagnosis of low-grade TC metastasizing to cervical lymph nodes (LN), which an oncologist faces. Primary ultrasonography (USG) of the neck is noted to have a low quality. The authors propose to use repeat (duplicate) USC of the neck during the clarifying diagnosis of TC and their developed method for USG of the cervical LN and the improved technique for determining the level of thyroglobulin in the cervical LN biopsy specimens. Introduction of these techniques could improve the preoperative diagnosis of low-grade TC metastases to the cervical LN.